2023
DOI: 10.1007/s13402-022-00754-w
|View full text |Cite
|
Sign up to set email alerts
|

Protamine 1 as a secreted colorectal cancer-specific antigen facilitating G1/S phase transition under nutrient stress conditions

Abstract: Purpose Cancer testis antigens (CTAs) are optimal tumor diagnostic markers and involved in carcinogenesis. However, colorectal cancer (CRC) related CTAs are less reported with impressive diagnostic capability or relevance with tumor metabolism rewiring. Herein, we demonstrated CRC-related CTA, Protamine 1 (PRM1), as a promising diagnostic marker and involved in regulation of cellular growth under nutrient deficiency. Methods Transcriptomics of five paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Moreover, we observed that PRM1 expression positively correlates with circANXA4 expression, while inversely correlates with miR-1256 expression. This echoes the study reporting that PRM1 is secreted antigen to facilitate G1/S phase transition to respond to nutrient stress in CRC cells [ 14 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, we observed that PRM1 expression positively correlates with circANXA4 expression, while inversely correlates with miR-1256 expression. This echoes the study reporting that PRM1 is secreted antigen to facilitate G1/S phase transition to respond to nutrient stress in CRC cells [ 14 ].…”
Section: Discussionsupporting
confidence: 79%
“…How these critical cancer-related factors interact to regulate CRC progression is unexplored. Furthermore, protamine1 (PRM1) facilitates G1/S phase transition in CRC cells by activating PI3K/AKT/mTOR pathway [ 14 ].…”
Section: Introductionmentioning
confidence: 99%